ANALISIS REAKSI PASAR ATAS PENGUMUMAN STOCK SPLIT SELAMA MASA PANDEMI COVID 19 (STUDI PADA PERUSAHAAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA) - Sedana, I Made Widi; Mertha, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024DO - 10.24843/EEB.2024.v13.i10.p13, 2024)
This study looked at how the market responded to company announcements of stock splits made during the COVID-19 epidemic. This test was repeated since there were more prospective investors and many issuers divided their shares as a result of the COVID-19 epidemic, which increased the number of corporate activities. This study was.carried.out at the Indonesia Stock Exchange, and samples from 21 businesses were selected using a purposive sampling strategy and a.non probability sampling method. An event window of seven days is used in this investigation. The documentary methodology was employed in this study to collect data. Quantitative data was employed in this study, and secondary data sources were chosen as the type of data. The data analysis approach. According to the analysis's findings, there was a market response to the news of the stock split during the COVID-19 epidemic, as shown by abnormal returns. This demonstrates that company stock split announcements have a considerable beneficial informational impact on investor perceptions and decision making in the capital market. A company's shares are more liquid when there are more transactions on them .